Study on the Optimization and Expansion of the Architectural Design Process by BIM Technology - Gang, Xiaoning (International Journal of Natural Resources and Environmental Studies, 2024)
In the contemporary realm of architecture, Building Information Modeling (BIM) technology is gradually reshaping the holistic management of architectural design, construction, and operation with its distinctive advantages. Despite the widespread adoption of BIM technology, numerous challenges persist in its practical implementation, such as the prevalence of information silos and hindered collaborative workflows. These impediments constrain the further advancement of BIM technology, consequently jeopardizing the quality and efficiency of architectural projects. Confronted with this reality, there exists a pressing need to delve deeply into the optimization pathways of BIM technology in the architectural design process, aiming to devise effective remedial strategies. This article will embark from the current application status of BIM technology in architectural design, expounding upon the fundamental principles, scope of application, and optimization strategies of BIM technology. Through this analysis, it seeks to explore avenues for maximizing the utilization of BIM technology in optimizing architectural design processes, thereby enhancing the overall quality and efficiency of architectural projects. This study not only contributes to propelling technological innovation within the architecture industry but also furnishes novel perspectives and directions for subsequent related research endeavors.